TEKNIK PENGGUNAAN AJIR PADA BUDIDAYA TANAMAN UBI JALAR (Ipomea batatas . L ) DI KAMPUNG BERSEHATI DISTRIK TANAH MIRING - Rahawarin, Beatrix Anna Maria (STIPER Santo Thomas Aquinas Jayapura, 2023)
Sweet potato (Ipomea batatas.L) is a plant belonging to the Convolvulacea family, thought to have originated from the Americas. Currently, Indonesia is the third sweet potato producing country in the world after China and Uganda with a production of 2,297 million tons. In addition to the vitamins and minerals, the nutritional content contained in sweet potatoes is protein, fat, crude fiber, calories, and ash. The specialty of sweet potato lies in its high β-carotene content. The potential for sweet potato to be developed in eastern Indonesia is very large, especially in Papua. Currently the Merauke Regency Government is trying to continue to develop sweet potatoes as one of the superior products in Merauke because Merauke Regency has generally a large land area, with great potential for the development of these sweet potatoes. The area for sweet potato development is in almost all districts in Merauke, but the biggest development so far has been in the Tanah Miring District with a production output of 5,065.10 tons. The purpose of this study was to determine the growth and development and production of sweet potatoes using a stake technique. The results of this study are expected to be information material for farmers and society in general. Data collection was carried out by observation with direct observation in the research area, including vegetative and generative growth variables. Overall, the vegetative and generative growth data show that the use of the Triangle stake gives the best results.